Fuzzy expert system for coronary heart disease diagnosis in Jordan - Alqudah, Ali Mohammad (Health and technology, 2017)
According to recently published research survey, Coronary Heart Diseases (CHD) are becoming a major severe health problem for Jordanians, where the number of deaths by CHD is 4329 out of 22,784 deaths in Jordan which forms a percentage of 18.8%. More specifically, CHD accounted for 18% of the overall mortality in Jordan. Using a fuzzy logic system which is a common approach for computing based on “degrees of truth” or non-crisp values. Nowadays, applying advanced computer technology systems in the medicine fields for diagnosis and treatment purposes is becoming more common for accuracy analysis. Therefore, the aim of this study is to detect heart diseases in subjects by using Fuzzy Expert System using visual studio 2010 with C#. A windows application fuzzy-based system was applied to diagnose the severity of the heart disease of a patient using existing data in the common medical records in Jordan. The results show that the system can be efficiently used for diagnosing the Chronic Heart Disease (CHD) based on the medical records in Jordan. The results demonstrate that the system has the high ability to diagnose the patient based on the records with a high percentage of accuracy.